AGRARIAN CONFLICT IN STATE-OWNED PLANTATION (A STUDY OF AGRARIAN CONFLICT IN MEKAR JAYA VILLAGE, LANGKAT REGENCY, NORTH SUMATRA PROVINCE) - Mujahid Widian Saragih; Gusti Pirandy (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze agrarian conflicts in state-owned plantations, specifically in Mekar Jaya Village, Langkat Regency, North Sumatra Province. North Sumatra is one of the provinces with the highest number of agrarian conflicts in Indonesia. Agrarian conflicts are a serious and urgent issue because it affects stakeholders’ social, economic and cultural lives. This study uses a descriptive-qualitative approach and focuses on the government’s role in handling the conflict through policy, both at the level of regulation and implementation. In addition, this study also relates the case to the theory of land grabbing, including examining the involvement of various stakeholders in it. The results of the study show that land grabbing in Mekar Jaya Village has triggered depeasantization. Furthermore, the dimension of agrarian conflict in the plantation sector is very complex because it involves many stakeholders. This study also found that despite the existence of conflict resolution mechanisms, these are not well implemented due to strong sectoral egos between government institutions. In conclusion, without a strong political commitment from the government to resolve agrarian conflicts, it will be difficult to resolve the agrarian conflict in Mekar Jaya Village.